Analysis of The Noise Level of The Diesel Engine with 1100 RPM in The Indoor Condition - Nanang Qosim (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
One of the weaknesses of diesel engines that most users complain about is the vibration and the noise. Therefore, it is very important to know the noise level of an engine in a room to consider the allowed duration of the exposure time, which is the aim of this study. The instrument used in this study was the Sound Level Meter, by first determining the radius of the hemisphere used in determining the location for the data collection. The measurement was carried out four times, where the largest value was considered as the main data, at four points. The result in this study indicated that the noise level of the diesel engine with a speed of 1100 rpm was 92.805 dBA with the background noise in the diesel engine room of 51.6 dB. Based on government regulations, the maximum exposure time to the noise at this level is 2 hours.